2017
DOI: 10.1016/j.prevetmed.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sheep farmer attitudes, beliefs, emotions and personality, and their barriers to uptake of best practice: The example of footrot

Abstract: There is interest in understanding how farmers’ behaviour influences their management of livestock. We extend the theory of planned behaviour with farmers attitudes, beliefs, emotions and personality to investigate how these are associated with management of livestock disease using the example of footrot (FR) in sheep.In May 2013 a one-year retrospective questionnaire was sent to 4000 sheep farmers in England, requesting data on lameness prevalence, management of footrot, farm/flock descriptors, and farmer-ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 65 publications
3
79
0
Order By: Relevance
“…A recent study conducted on sheep farmers’ response to foot rot focused on the effects of personality, emotions such as empathy and general attitude on the treatment strategy. The authors found that sheep had an increased risk of lameness when their farmers demonstrated negative emotions and hopelessness toward foot rot, and that farmers’ personality and emotions are associated with their differences in management of foot rot (O’Kane et al, 2016). …”
Section: Factors Influencing Antimicrobial Use: the Crucial Issue Of mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted on sheep farmers’ response to foot rot focused on the effects of personality, emotions such as empathy and general attitude on the treatment strategy. The authors found that sheep had an increased risk of lameness when their farmers demonstrated negative emotions and hopelessness toward foot rot, and that farmers’ personality and emotions are associated with their differences in management of foot rot (O’Kane et al, 2016). …”
Section: Factors Influencing Antimicrobial Use: the Crucial Issue Of mentioning
confidence: 99%
“…Furthermore, recent research suggests that a deep understanding of the decision making process is needed, as it can explain success or failure of policy interventions (Rat-Aspert and Fourichon, 2010; Garforth, 2015; O’Kane et al, 2016). …”
Section: Priority Actions To Minimize the Impact Of Veterinary Antimimentioning
confidence: 99%
“…O'Kane et al, 2016) and so the interventions could not lead to further change in behaviour or reduction in prevalence of lameness. Flocks with prevalence of lameness >15% in 2013 were also excluded because such a high prevalence of lameness is indicative of an outbreak of infectious lameness which would not be resolved by adopting the intervention message…”
mentioning
confidence: 99%
“…That treatment, when administered within 3 days of onset of lameness (3,5), is current "best practice" because it minimizes the adverse effects from footrot on the individual sheep (3), reduces repeat cases of disease (7) and onward spread of disease (8). Current "best practice" has been promoted since 2006, and by 2013 11% of English farmers were using the new "best practice" (9).…”
Section: Introductionmentioning
confidence: 99%
“…This included continuing to trim hoof horn to expose diseased tissue (therapeutic foot trimming) without use of an antibiotic injection to treat footrot. In addition, many farmers did not treat lame sheep within 3 days of onset of lameness, explained in part by farmers not prioritizing lameness all year round and not treating lame sheep at all during the mating season and late pregnancy (9). O'Kane et al (9) proposed that feelings of hopelessness reported by farmers could trigger 1 https://assets.publishing.service.gov.uk/government/uploads/system/uploads/ attachment_data/file/69365/pb5162-sheep-041028.pdf inactivity in managing lameness and create a cycle of selffulfilling behavior, and that farmers' ability to act appropriately toward footrot was predicted in part by their perceived behavioral control, this has been reported for other animal diseases (19,20).…”
Section: Introductionmentioning
confidence: 99%